A NEW INDIGENOUS CYANOMETHANE-DEGRADING BACTERIUM ISOLATED FROM GOLD MINING WASTE WATER - Sulistinah, Nunik; Munandar, Hendra; Sunarko, Bambang (JURNAL BIOLOGI INDONESIA, 2019)
ABSTRACT The gold mining wastewater effluent is potential source for isolating cyanides-degrading bacteria, since cyanide is commonly used in gold extraction process in the mining industry. An indigenous bacterial strain LP3, capable of growing on and utilizing of a high concentration of cyanomethane (up to 1.0 Molar), could be isolated from Cikotok gold mine effluent. Based on 16S rDNA sequence, the strain was identified as Rhodococcus pyridinivorans. During the growth on cyanomethane (CH3CN), ethanamide (CH3ONH2) and ethanoic acid (CH3COOH) were detected in the growth media, indicating that nitrile hydratase and amidase involved in the metabolism of the substrate. The involvement of both enzymes on the conversion of cyanomethane was also proved by our study on cyanomethane biodegradation using whole cells of R. Pyridinivorans LP3. Besides cyanomethane, the R. pyridinivorans LP3 could also utilize various aliphatic, aromatic, heterocyclic nitriles and amides as growth substrates. Base on these results, R. pyridinivorans LP3 is expected to be used as a potential candidate for biological treatment for cyanide-containing wastes, although further research is still needed, before being applied on a field scale.  Keywords: biocatalyst, cyanide degrading bacteria, gold mining, Rhodococcus pyridinivorans LP3